1993
DOI: 10.1093/carcin/14.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations of p53 gene in human hepatocellular carcinoma from China

Abstract: Allele losses and mutations have been examined in 38 cases of primary hepatocellular carcinomas (HCC) from different geographic areas of China by Southern, single-strand conformational polymorphism (SSCP) and direct DNA sequencing analyses. Two of 12 samples from Qi-Dong and six of 18 HCCs from Shanghai showed loss of heterozygosity (LOH) at the loci on chromosome 17p13.3. All of the nine mutations in the p53 gene detected in HCC from Qi-Dong were clustered at the third base of codon 249, i.e. G:C to T:A, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…In geographical areas of AFB 1 dietary exposure (a mycotoxin contaminating foods like corn, rice and peanuts) and chronic viral hepatitis, like China and Africa, a point mutation at the third position of codon 249 ser resulting in a G:C to T:A transversion was common in HCC (Figure 1a-c) (Bressac et al, 1991;Hsu et al, 1991). These results have been confirmed and extended by others (Scorsone et al, 1992;Li et al, 1993;Lunn et al, 1997). This codon 249 mutation can also be detected in serum DNA from patients from the Gambia with HCC, so that TP53 mutant DNA may be a biomarker of exposure to AFB 1 and possibly early HCC (Kirk et al, 2000).…”
Section: Aflatoxin Bsupporting
confidence: 62%
“…In geographical areas of AFB 1 dietary exposure (a mycotoxin contaminating foods like corn, rice and peanuts) and chronic viral hepatitis, like China and Africa, a point mutation at the third position of codon 249 ser resulting in a G:C to T:A transversion was common in HCC (Figure 1a-c) (Bressac et al, 1991;Hsu et al, 1991). These results have been confirmed and extended by others (Scorsone et al, 1992;Li et al, 1993;Lunn et al, 1997). This codon 249 mutation can also be detected in serum DNA from patients from the Gambia with HCC, so that TP53 mutant DNA may be a biomarker of exposure to AFB 1 and possibly early HCC (Kirk et al, 2000).…”
Section: Aflatoxin Bsupporting
confidence: 62%
“…Dimethylbenzanthracene (DMBA) causes primarily base pair substitutions, predominantly A:T 3 T:A (44%) and G:C 3 T:A (24%) [Manjanatha et al, 2000]. In human populations, signature mutations associated with specific exogenous mutagens have been observed in samples of somatic mutations in the p53 tumor-suppressor gene [Harris and Hollstein, 1993;Hussain and Harris, 1999], for example, G 3 T transversions in lung cancers of cigarette smokers [Chiba et al, 1990], C 3 T and CC 3 TT tandem dipyrimidine transitions in skin cancers associated with excessive sun exposure [Brash et al, 1991], and G 3 T transversions at arginine 249 in liver cancers associated with aflatoxin exposure [Bressac et al, 1991;Hsu et al, 1991;Scorsone et al, 1992;Aguilar et al, 1993;Li et al, 1993]. Such signature mutations can be detected in the mutation pattern with high sensitivity.…”
Section: Signature Mutations Permit Identification Of Mutagensmentioning
confidence: 99%
“…In recent years, direct examination of known oncogenes/TSGs has been used to explore the genes related to liver tumorigenesis [10]. Results of previous studies showed a variation of p53 mutations from various areas in terms of frequency, spectrum and timing: mutation of codon 249 is associated with AFB1 exposure in rural regions of China (Qidong) and Africa (Mozambique and Senegal) and may represent an early event during hepatocarcinogenesis, whereas different mutation spectrum of p53 was observed in Japan and big cities of China(Shanghai and Beijing) [11][12][13]. In addition, activation or DNA amplification of c-myc and cyclin D, mutations of ÎČ-Catenin and IGFIIR/M6P have been observed in HCC [14][15][16].…”
Section: Introductionmentioning
confidence: 99%